2014
DOI: 10.1093/cvr/cvu205
|View full text |Cite
|
Sign up to set email alerts
|

Study familial hypertrophic cardiomyopathy using patient-specific induced pluripotent stem cells

Abstract: AimsFamilial hypertrophic cardiomyopathy (HCM) is one the most common heart disorders, with gene mutations in the cardiac sarcomere. Studying HCM with patient-specific induced pluripotent stem-cell (iPSC)-derived cardiomyocytes (CMs) would benefit the understanding of HCM mechanism, as well as the development of personalized therapeutic strategies.Methods and resultsTo investigate the molecular mechanism underlying the abnormal CM functions in HCM, we derived iPSCs from an HCM patient with a single missense mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
173
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(192 citation statements)
references
References 48 publications
13
173
1
2
Order By: Relevance
“…HCM iPSC-CMs exhibited structural abnormalities consistent with the HCM phenotype. Similar calcium-handling abnormalities were identiied, consistent with observations made from animal models [70]. These studies explored the possible patient-speciic and mutation-speciic disease mechanism of HCM and demonstrated the potential of using HCM iPSC-CMs for future development of therapeutic strategies.…”
Section: Ipsc-cmssupporting
confidence: 77%
See 1 more Smart Citation
“…HCM iPSC-CMs exhibited structural abnormalities consistent with the HCM phenotype. Similar calcium-handling abnormalities were identiied, consistent with observations made from animal models [70]. These studies explored the possible patient-speciic and mutation-speciic disease mechanism of HCM and demonstrated the potential of using HCM iPSC-CMs for future development of therapeutic strategies.…”
Section: Ipsc-cmssupporting
confidence: 77%
“…iPSC-CMs derived from a patient with HCM caused by the MYH7 mutation p.Arg442Gly and mutation p.Arg663His have demonstrated the pathogenic efects [69,70]. HCM iPSC-CMs exhibited structural abnormalities consistent with the HCM phenotype.…”
Section: Ipsc-cmsmentioning
confidence: 95%
“…The latter observation provided mechanistic validation that Ca 2ϩ handling defects and elevated intracellular Ca 2ϩ levels are underlying disease mechanisms for HCM. Whole transcriptome sequencing and pathway enrichment analysis in HCM hiPSC-CMs also showed a widespread enrichment of genes associated with cellular proliferation (e.g., WNT1), Notch signaling (e.g., DLL1/4), and FGF signaling (e.g., FGF8/FGFR4) which could serve as potential therapeutic targets (89). HCM manifestations associated with the multi-organ condition known as LEOPARD syndrome were likewise studied in a hiPSC-CM platform, showing that irregularities in RAS-MAPK signal transduction are implicated in development of disease pathology (31).…”
Section: B Cardiomyopathiesmentioning
confidence: 95%
“…It should be noted that the R173W mutation identified in these DCM patients had not been previously reported, and was discovered in this family cohort following exome sequencing of the skin fibroblasts used to generate hiPSCs. In separate studies, hiPSC-CMs carrying DCM-associated mutations in the spliceosome RNA-binding motif protein 20 (RBM20), lamin A/C (LMNA/C), or desmin (DES) genes (243,275,304) also demonstrated abnormalities that closely recapitulate the morphological and functional phenotypes of the affected human heart, as outlined in hiPSC models of HCM associated with thick myofilament myosin heavy chain 7 (MYH7) (89,148) or myosin binding protein C3 (MYBPC3) (262) mutations showed that in vitroderived hiPSC-CMs are significantly enlarged, as seen in the diseased human myocardium. hiPSC-CMs also demonstrated increased myofibril content, contractile arrhythmias (DADs), Ca 2ϩ cycling perturbations, and intracellular Ca 2ϩ elevation, which were worsened by adrenergic stimulation (e.g., with isoproterenol) or environmental exposure to the potent vasoconstrictor endothelin-1 (ET-1) (310).…”
Section: B Cardiomyopathiesmentioning
confidence: 98%
“…Induced pluripotent stem cells using CB can be used for disease modelling, drug discovery, drug screening, cell replacement therapy and tissue regeneration [48][49][50][51][52][53][54][55][56][57][58]. Due to many properties, CB is a valuable source for iPSCs production and approximately 80-100 ml of CB contains about one billion cells which can be collected safely and easily from umbilical cord [59] and have promising future for regenerative and personalized medicine [48].…”
Section: Future Perspectivesmentioning
confidence: 99%